SAT0023 Artery Tertiary Lymphoid Organs Occur in Giant Cell Arteritis. (15th July 2016) - Ciccia, F.; Rizzo, A.; Alessandro, R.; Guggino, G.; Croci, S.; Raimondo, S.; Cavazza, A.; Salvarani, C.; Triolo, G.
Abstract : Background: Arteries are immuno-privileged sites. In advanced atherosclerotic lesions, however, adventitial lymphoid infiltrates, sometimes aggregated in lymphoid follicles (the so called artery tertiary lymphoid organs, ATLO), occur together with marked neoangiogenesis and lymphangiogenesis, and with the extensive induction of high endothelial venules. Objectives: To investigate if tertiary lymphoid organs (TLO) are present in GCA and their formation is associated with the ectopic expression of constitutive lymphoid tissue-homing chemokines. Methods: RT-PCR, immunohistochemical and immunofluorescence analysis were used to determine the presence of ectopic TLO in GCA and the expression of chemokines/chemokine receptors and cytokines involved in lymphoneogenesis in the artery samples obtained from 50 GCA patients and 30 controls. The presence of lymphatic conduits, of follicular dendritic cells (FDC) precursors and lymphoid tissue inducer cells was also investigated. Finally, expression of CXCL13 and BAFF by isolated vascular smooth muscle cells was evaluated before and after stimulation with toll like receptors agonists and cytokines. Results: Artery TLO (ATLOs) were observed in the media layer of 60% of GCA patients in close proximity to neo-formed PNAD+ high endothelial venules. Pesence of ATLOs was independent by the number of infiltrating mononuclear cells, the age of patients and the presence of atherosclerosis. ATLO formation was also accompanied by the expression of CXCL13, BAFF, APRIL, IL-7 and IL-17. CXLC13 and BAFF expression was manily observed in the context of ATLOs, in VSMC and endothelial cells of neo-formed high endothelial cells. IL-7 and IL-17 expression levels were significantly correlated with the levels of CXCL13 and BAFF. The presence of follicular dendritic cells (FDC) precursors and of lymphoid conduits was demonstrated by confocal microscopy analysis and immunohistochemistry, respectively. Stimulation of VSMC with TLR agonists (LPS and poly-IC) and pro-inflammatory cytokines (IL-1b, IL-6, IFN-g and IL-17) resulted in the up-regulation of BAFF and CXCL13. Conclusions: ATLOs occur in the inflamed arteries of GCA patients possibly representing the immune sites where immune responses toward unknown arterial wall-derived antigens may be organized. Disclosure of Interest: None declared